Cancellation of Registration of Changes to the Articles of Association of a Limited Liability Company Due to the Lack of Transfer of Shares to the Heirs Due to the Death of the Shareholders - Takarub, Kukuh Derajat (Formosa Journal of Science and Technology, 2024)
Conflicts among shareholders are considered to be close firms' weak point. They can take many various forms, but they typically manifest as shareholder impasses, minority mistreatment, or persecution of the majority. The behavioral law and economics movement, which is now very popular, demonstrates how many cognitive biases and heuristics—such as information asymmetry, availability and representativeness heuristics, over-optimism, and strategic behavior—contribute to their genesis. Depending on the specific governance objective to be met, entrepreneurs use a variety of contractual protections in international corporation law practice to successfully avoid and settle the aforementioned shareholder conflicts. The most prevalent are limitations on share transfers (such as permission clauses and the right of first refusal), special rights for minority shareholders (such as the ability to veto management decisions, and super-majorities for important.